ANALYSIS OF THE TECHNICAL EFFICIENCY OF AQUACULTURE POND ENTERPRISES IN TANI BARU VILLAGE ANGGANA DISTRICT KUTAI KARTANEGARA REGENCY - Novia Ramadayanti; Erwan Sulistianto Erwan; Heru Susilo Heru (Universitas Mataram, 2026)
This study aims to analyze the level of efficiency of pond aquaculture enterprises and to identify the factors that influence the efficiency of pond farming businesses in Tani Baru Village, Anggana District. This study employed a survey method using purposive sampling to determine respondents based on the Slovin formula. Data were analyzed using the Data Envelopment Analysis (DEA) method with the Constant Return to Scale (CCR) and Variable Return to Scale (BCC) models,and the factors influencing efficiency were analyzed using Tobit regression analysis. The results showed that the average efficiency values in the CCR model were Technical Efficiency (TE) of 0.067, Allocative Efficiency (AE) of 0.693, and Cost Efficiency (CE) of 0.031. Meanwhile, in the BCC model, the results obtained were Technical Efficiency (TE) of 0.152, Allocative Efficiency (AE) of 0.642, and Cost Efficiency (CE) of 0.092. The results of the Tobit regression analysis indicated that business experience and land area had a significant effect on the efficiency of pond aquaculture businesses, whereas age and education did not have a significant effect.